الممالك اليمنية القديمة - شلالقة, السعيد (جامعة الوادي University of Eloued, 2017)
يعتبر أهل اليمن القديم من أبرز شعوب شبه الجزيرة العربية القديمة مكانة حضارية ، حيث تميزوا بالسبق الحضاري عن مجتمعات المنطقة في عصورها القديمة ، و قد ساعدتهم عوامل متباينة لإنجاز و إبراز الإنتاج الحضاري اليمني المتنوع ، و من مظاهر ذلك تمكن اليمنيون القدامى تأسيس العديد من الممالك القديمة التي ساهمت في تطوير الحضارات الكثيرة التي عرفتها منطقة جنوب شبه الجزيرة العربية . Old family Yemen considers from produced people comparable with of Arabian peninsula old civilized standing , where the civilized antecedence about societies of the area in her old eras be distinguished in , and helped them different laborers to accomplishing and showing of civilized showing the production the assorted Yemeni , and from appearances that the old Yemeni managed establishment many from the kingdoms old which development of the civilizations contributed in many which introduced her area south of comparable with of Arabian peninsula .
Keywords: شبه الجزيرة العربية ، اليمنيون القدامى